Brightest Stars: The Falling - Book 1 - Todd, Anna (Toronto, ON : Wattpad Books, Frayed Pages, 2022)
"Twenty-year old Karina is proud of the independent life she is trying to create for herself in Fort Benning, Georgia. A dutiful daughter, supportive sister to a troubled twin brother, and caring friend to her roommate, Elodie, she always puts the needs of others ahead of her own, and prides herself on being a fixer of broken things--whether it's the house she's just bought or the fragmented family she works hard to keep intact. Like anyone who has grown up around an army base, Karina also knows the background noise that follows men and women home from war. And when she meets Kael, a handsome soldier on the cusp of discharge, she's immediately intrigued by his brooding presence and enigmatic silence. As their uncertain and unexpected friendship starts to turn into something more, Karina tries to piece together Kael's story: he is emotionally closed off, recovering from wounds and other trauma in the aftermath of two deployments in Afghanistan. In her practice as a physical therapist, Karina has a strong desire to help him heal, and though it challenges her many insecurities and anxieties, she has an equally strong desire to trust him. But that trust is fragile, like the preciousness of a soldier's life. It can be gone in an instant. Ultimately facing a crossroads, Karina and Kael find their relationship will be tested by the one thing that Karina cannot accept, forgive, or understand"--
Keywords: Daughters -- Fiction; Twins -- Fiction; Female friendship -- Fiction; Friendship -- Fiction; Roommates -- Fiction; Families -- Fiction; Man-woman relationships -- Fiction; Soldiers -- Fiction; Fort Benning (Ga.) -- Fiction; Romance fiction